Attenuation of wave energy in mangrove forests - Narra, Pedro Miguel Fragoso (2013)
Mangrove forests are a very important ecosystem in protected coastal zones. These forests provide food and habitat for numerous species and have an important role in the coastal stabilization, trapping sediments and reducing erosion. They also contribute to wave attenuation, which might add to the safety of a coastal environment. Although the importance of mangrove forests in wave attenuation is widely recognized, the amount of comprehensive studies to understand the quantitative effect of the mangroves in the attenuation of wave energy is still insufficient. This thesis aims to increase knowledge on wave attenuation in mangroves by studying this process in the field. Results are presented of a fieldwork campaign executed in the Trang province, Thailand, between November 2010 and May 2011. It is the first known study that includes quantitative information on the vegetation in the field, presenting rates of vegetation density along the studied transects. Two different transects were chosen in Trang province – Kantang and Palian – showing differences in slopes and vegetation. Measurements included surface elevation, vegetation density and pressure fluctuations. After the measurements, the pressure data was carefully selected and analyzed using spectral analysis and wave linear theory concepts. The entire procedure is described in this thesis in order to provide a good basis for future studies in the field. The results show the presence of waves with periods mostly exceeding 5 seconds. At Kantang most of the waves have periods between 10 and 20 seconds. Wave attenuation is found to be about 2.5 J/m2 in 100 meters of mangrove forest at Palian and 0.8 J/m2 per 100 meters of mangroves at Kantang. This difference can be explained by a more accentuated slope, a denser forest and the presence of higher frequency waves that are easily attenuated at Palian. In general, the wave attenuation reaches values around 60% attenuation along the transects. Comparison with other studies shows that the results in this thesis resemble the findings of previous researches. The wave attenuation in mangroves was also compared to wave attenuation in salt marshes and it was concluded that the salt marshes have better wave attenuating capacity if the water depth is not too high, but with increasing water depths they rapidly loose this capacity, in contrary to mangroves.